2013
DOI: 10.1001/jamaneurol.2013.658
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-Related Neuropathy

Abstract: The newly recognized entity IgG4related disease (IgG4-RD) is characterized by an elevated IgG4 serum concentration and tissue infiltration by IgG4-positive plasma cells. We describe, for the first time, the clinical features and nerve biopsy findings of a patient with IgG4-RD who presented with neuropathy in the extremities.Observations: A 55-year-old man had histopathologically defined IgG4-RD that manifested as sensorymotor neuropathy. The neuropathic features were multiple mononeuropathies with electrophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 11 publications
1
27
2
Order By: Relevance
“…Our case is different from previous reports of IgG4-RD peripheral nervous system involvement, which seem to reveal 2 patterns: the first pattern is of an asymmetrical axonal peripheral neuropathy 13,14 suggestive of mononeuritis multiplex with elevated inflammatory markers. Sural nerve biopsy in a classical case 13 revealed infiltration of IgG4+ plasma cells and fibrosis in the epineurium, whereas in another case 14 showed tumefactive lymphoid infiltrates without IgG4+ plasma cells or fibrosis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our case is different from previous reports of IgG4-RD peripheral nervous system involvement, which seem to reveal 2 patterns: the first pattern is of an asymmetrical axonal peripheral neuropathy 13,14 suggestive of mononeuritis multiplex with elevated inflammatory markers. Sural nerve biopsy in a classical case 13 revealed infiltration of IgG4+ plasma cells and fibrosis in the epineurium, whereas in another case 14 showed tumefactive lymphoid infiltrates without IgG4+ plasma cells or fibrosis.…”
Section: Discussioncontrasting
confidence: 99%
“…Putative mechanisms of peripheral neuropathy in IgG4-RD include focal ischemia resulting from occlusion of vessels by infiltrating inflammatory cells or from constriction by marked fibrosis. 13 In our case, the prebiopsy treatment with steroids probably masked the pathologic findings and resulted in significant clinical improvement.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…To the best of our knowledge, there is only a single report of neuropathy ascribed to IgG4-RD [101]. The authors described a 55-year-old man with histopathologically confirmed IgG4-RD manifesting as mononeuritis multiplex, with electrophysiological findings suggestive of axonal neuropathy.…”
Section: Igg4-related Neuropathy and Perineural Diseasementioning
confidence: 99%
“…However, IgG4-RD rarely involves peripheral nerves. There have been a few reported cases involving the peripheral nervous system, which were characterized by nerve-centered distinct soft tissue masses (4,5).…”
Section: Introductionmentioning
confidence: 99%